Global and regional incidence of intrahepatic cholestasis of pregnancy: a systematic review and meta-analysis - Ali Jamshidi Kerachi; Mohammad Amin Shahlaee; Pardis Habibi; Niloofar Dehdari Ebrahimi; Moein Ala; Alireza Sadeghi (BMC Medicine)
Abstract Background Intrahepatic cholestasis of pregnancy (ICP) can be a source of significant distress for both pregnant women and the fetus, impairing the quality of life and well-being of pregnant women, leading to psychological disorders among pregnant women with severe or recurrent ICP, and causing life-threatening complications among fetuses. Regrettably, our current understanding of ICP globally is limited, lacking a comprehensive estimation of its incidence. Therefore, in this systematic review and meta-analysis, we aimed to investigate the global and regional incidence of ICP and identify factors that account for its variety across studies. Methods A comprehensive search strategy was implemented across PubMed, Scopus, and Web of Science databases. To stabilize the variance, the Freeman-Tukey double arcsine transformation was employed. Subgroup analyses were conducted based on continent, publication type, study design and timing, regional classifications, developmental status, and World Bank income grouping. A multivariate meta-regression analysis was performed to estimate the effects of the continuous moderators on the effect size. Results A total of 42,972,872 pregnant women were analyzed from 302 studies. The overall pooled incidence [95% confidence interval] of ICP was 2.9% [2.5, 3.3]. Studies with larger sample sizes tended to provide significantly lower estimates of ICP incidence: 1.6% [1.3, 2] vs 4.7% [3.9, 5.5]. Asia had the highest incidence of ICP among the continents, whereas Oceania had the lowest. Countries that were classified as developed and with higher income had a lower incidence of ICP than those classified as developing and low and middle income. Conclusions The findings of this study will provide valuable insights into the current knowledge regarding the association of the quality of public health and socioeconomic variations with the incidence of ICP on a global scale. Graphical Abstract